Investigação sobre a utilização do Programa GESPÚBLICA em instituição voltada para ciência, tecnologia e saúde: um estudo de caso na Fundação Oswaldo Cruz - Ayres, Ana Beatriz Nascimento (2012)
Over the years, for their survival and growth, organizations must recognize the organizational challenges to uncover new opportunities and take the appropriate management response to the necessary changes. At the heart of this discussion, a special focus has been given to the excellence of public services to citizens. In the face of social demands, public administration seeks to improve services and civil servants to develop new models and management practices. It was chosen a theoretical-methodological basis to understand how governance evolved in Brazil, starting on the patrimonial, bureaucratic, managerial models, and finally returning to the quality of public services and the implementation of an excellence model for public service. Therefore, the concepts that have developed a set of variables already standardized for research have been used. This study sought to identify and analyze the results of applying the Excellence Model in Public Management (MEGP) at Oswaldo Cruz Foundation (Fiocruz), according to the National Public Management (Gespública) MOP, vis a vis the organizational guidelines, and investigate the motivations and inhibitions to adhere to it. The case study was conducted from 2003 to 2011. The researched institution was chosen because it undertakes efforts to improve and professionalize the management in pursuit of improved services to society. The data analysis technique used was content analysis under Bardin’s perspective, in order to understand the information and establish the theoretical foundations of research concepts. The survey results indicate that the institution leads to the partial fulfillment of the program’s goals, because it was possible to verify improvements resulting from its implementation, but it can only fulfill its objectives completely if the best practices are introduced in its routine and culture and the focus on results is consolidated.